Endophytic colonization of sugarcane (Saccharum officinarum)by the novel diazotrophs Shinella sp. UYSO24 and Enterobacter sp. UYSO10 - Taulé, C.; Castillo, A.; Villar, S.; Olivares, F.; Battistoni, F.
Aims Sugarcane is a multipurpose crop mostly used in Uruguay for bioethanol production. It requires high amounts of N fertilization for optimal growth, which causes environmental degradation and high production costs. Previously, a bacterial collection associated with surface-sterilized stems of sugarcane was characterized for in vitro plant growth-promoting (PGP)traits. The aims of this study were (1)to determine if selected isolates from the collection are sugarcane growth promoters and (2)to determine if they are true endophytes of sugarcane. Methods Plant growth promotion assays were used to study the effects of selected isolates on sugarcane plantlets. Light microscopy, transmission electron, and scanning electron microscopy (TEM, SEM)were employed to describe the structure of the interaction between the plant growth-promoting bacteria and the plants. qPCR was used to quantify the bacteria residing in the inner plant tissues. Results Enterobacter sp. UYSO10 and Shinella sp. UYSO24 were confirmed to have a PGP effect on the commercial sugarcane cv. LCP 85384. Both strains were defined as true endophytes of sugarcane plants with this being the first case for a strain in the genus Shinella in grasses. Conclusions These data will contribute to the final development of a sugarcane PGP inoculant based on endophytic plant growth-promoting bacteria.
Keywords: ENTEROBACTER; SHINELLA; SUGARCANE; ENDOPHYTE; PLANT GROWTH PROMOTION; ELECTRON MICROSCOPY